2016
DOI: 10.4049/jimmunol.1600815
|View full text |Cite
|
Sign up to set email alerts
|

Rpl22 Loss Selectively Impairs αβ T Cell Development by Dysregulating Endoplasmic Reticulum Stress Signaling

Abstract: While ribosomal proteins (RP) are thought to primarily facilitate biogenesis of the ribosome and its ability to synthesize protein, emerging evidence suggests that individual RP can perform critical regulatory functions that control developmental processes. We showed previously that despite the ubiquitous expression of the RP, Rpl22, germline ablation of Rpl22 in mice causes a selective, p53-dependent block in the development of αβ, but not γδ, T cell progenitors. Nevertheless, the basis by which Rpl22 loss se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…Through applying a XBP-1-GFP reporter system, researchers revealed that the IRE-1α-XBP-1 branch is active in CD4 + CD8 + T cells from the thymus, indicating a role of the UPR in T cell development [37]. Another study reported that ablation of Rpl22 (RP ribosomal protein L22), which restrains ER stress, blocked the development of αβ, but not γδ T cell progenitors [38]. On the other hand, T cells containing a point mutation in the Kdelr1 gene (encoding ER chaperone KDEL receptor 1) have higher levels of phospho-eIF2α and impaired T cell survival [39].…”
Section: The Role Of Upr In T Cells Under Physiological and Pathologimentioning
confidence: 99%
“…Through applying a XBP-1-GFP reporter system, researchers revealed that the IRE-1α-XBP-1 branch is active in CD4 + CD8 + T cells from the thymus, indicating a role of the UPR in T cell development [37]. Another study reported that ablation of Rpl22 (RP ribosomal protein L22), which restrains ER stress, blocked the development of αβ, but not γδ T cell progenitors [38]. On the other hand, T cells containing a point mutation in the Kdelr1 gene (encoding ER chaperone KDEL receptor 1) have higher levels of phospho-eIF2α and impaired T cell survival [39].…”
Section: The Role Of Upr In T Cells Under Physiological and Pathologimentioning
confidence: 99%
“…It has been demonstrated that eL22 (Rpl22) loss exacerbates ER stress and strongly activates two of the three ER stress-signaling pathways, PERK and IRE1α [ 60 ]. Zhang et al have shown that UPR induction promotes the interaction between the r-proteins (uL18/rpL5, uL5/rpL11 and uL14/rpL23) and Hdm2 in PERK-dependent manner.…”
Section: Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…RP defects or imbalances are associated with endoplasmic reticulum (ER) stress (Solanki et al., ), which is a known inducer of autophagy (Nie et al., ). In turn, ER stress triggers regulatory ubiquitination of 40S RPs (Higgins et al., ).…”
Section: Ribophagy and Cancermentioning
confidence: 99%